Análisis de las competencias pedagógicas y su relación con el perfil de egreso de los estudiantes del octavo semestre de la carrera de biología, química y laboratorio en el periodo marzo- julio 2015 - Guamán Lema, Mayra Fabiola (2016)
This research aims to: “Analysis of the pedagogical skills and relationship with the graduate profile in students of the eighth semester in the career of Biology, chemistry and Laboratory in the period March-July 2015”. The research problem is: Are there limitations to the analysis of the pedagogical skills and their relationship with the graduate profile of the eighth semester students in the career of biology, chemistry and Laboratory in the period March-July 2015? Today’s society requires competent teachers able to meet today’s educational problems, this is why the UNACH must develop these skills in future teachers. Competition is the comprehensive ability of a person to perform affectively in specific working and pedagogical situations, it is a built knowledge in formal and informal way; that is to say, is a dynamic, integrated, multidimensional process to achieve permanent professionalization. Teaching skills (Neuroliderazgo, Entrepreneurship interdisciplinary, Ecological,Assertive Communication) in teachers should have the consistency needed to meet the changing demands of today’s society in the field of education in which the procedural contents and pedagogical actions are platform to strengthen the most harmonious way to the integral formation. This work aims to socialize the analysis of pedagogical skills to contribute to the improvement of the graduate profile. The methodology of this research is quasi-experimental as we apply a survey before and after the investigation giving the following results, before the investigation only 28% have knowledge about skills, after the training 57% have knowledge about teaching skills, after the investigation it was concluded that the teaching skills contributed to the training of graduate students, this is why it is recommended to promote the importance of developing teaching skills in students in the during the career to improve the graduate profile of them.